Investigation of hydrogenation parameters influence on hydrogen sorption rate by Zr-1%Nb alloy with nickel layer; Известия вузов. Физика; Т. 58, № 9-3 - Kudiyarov V. N. Victor Nikolaevich; Kashkarov E. B. Egor Borisovich; Syrtanov M. S. Maksim Sergeevich; Babikhina M. N. Mariya Nikolaevna; Vlasov V. A. Viktor Alekseevich (2015, 2015)
Заглавие с экрана